ANALYSIS OF EEG IMAGES - DASSIOS, GEORGE; GIAPALAKI, SOFIA N.; KANDILI, ANASTASIA N.; KARIOTOU, FOTINI (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
The electric potential of the direct Electroencephalography (EEG) problem is presented for the case of a homogeneous sphere, when this is given both in closed form – exact solution – and in terms of spherical harmonics – approximate solution. The model in both cases involves a sphere with constant conductivity, where the source is considered to be a point current dipole. Data distribution of the electrical potential on the head surface is produced for both cases. The presentation includes a parametric analysis based on the location as well as on the orientation of the moment, for a single current dipole. A detailed comparison between the exact and the approximate solution is also included.